PEMBELAJARAN BAHASA ARAB DI KELAS 5 MADRASAH IBTIDAIYAH DARUL ULUM KOTA CIREBON SEMESTER GANJIL TAHUN AJARAN 2022/2023 - Alwi, Mohamad (FASHLUNA, 2022)
Arabic is a second language as well as a religious language for Indonesian people, so Arabic is the main subject for schools under the auspices of the Ministry of Religion. Learning Arabic in Madrasah Ibtidaiyah is the initial foundation for students in learning it, each school has differences in the teaching process. The purpose of this study is to explore and describe how Arabic is taught in Class 5 MI Darul Ulum's odd semester of the 2022/2023 academic year. This study uses qualitative methods with observation, interviews, and documentation techniques while the data analysis technique used in this study is interactive data analysis techniques. The results of this study are that learning Arabic in class 5 MI Darul Ulum is quite good, this is reflected in the learning process starting from the introduction, core, and closing activities. The competencies to be achieved include 4 maharah namely; maharah istima', maharah kalam, maharah qira'ah, andMaharajh kitabah in the learning process for each maharah is carried out in different ways including maharah istima' which is carried out by listening-repeating, listening to writing, debriefing and playing a roll. Maharah Kalam by means of groups and demonstrations. Maharah qira'ah by way of kulliyah and juziyyah. Maharah ketubah by means of controlled writing and guided writing. The media used are visual media, audio and audio visual. Meanwhile, the evaluation is carried out by means of oral and written tests.